Parenting children with ADHD 10 lessons that medicine cannot teach - Monastra, Vincent J. (American Psychological Association, 2014)
In this second edition, Dr. Vince Monastra provides practical, step-by-step guidance to parents looking for ways to bring out the best in kids with attention-deficit/hyperactivity disorder. He presents updated lessons aboutthe causes of ADHD, how medications work, and the problems that sleep deficits, poor nutrition, and other medical disorders can cause. He also shares his innovative approach for improving organization, task completion, problem solving, and emotional control.